2013
DOI: 10.1085/jgp.201310996
|View full text |Cite
|
Sign up to set email alerts
|

The G-protein–gated K+ channel, IKACh, is required for regulation of pacemaker activity and recovery of resting heart rate after sympathetic stimulation

Abstract: Parasympathetic regulation of sinoatrial node (SAN) pacemaker activity modulates multiple ion channels to temper heart rate. The functional role of the G-protein–activated K+ current (IKACh) in the control of SAN pacemaking and heart rate is not completely understood. We have investigated the functional consequences of loss of IKACh in cholinergic regulation of pacemaker activity of SAN cells and in heart rate control under physiological situations mimicking the fight or flight response. We used knockout mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
89
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 46 publications
8
89
0
Order By: Relevance
“…The muscarinic-gated K + channel (I KACh ) is involved in the negative chronotropic effect of the parasympathetic nervous system on heart rate (20,21). Two subunits of the G-protein activated inwardly rectifying K + channels (GIRK1 and GIRK4) of the GIRK/ Kir3 subfamily assemble as heterotetramers to form cardiac I KACh channels (22).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…The muscarinic-gated K + channel (I KACh ) is involved in the negative chronotropic effect of the parasympathetic nervous system on heart rate (20,21). Two subunits of the G-protein activated inwardly rectifying K + channels (GIRK1 and GIRK4) of the GIRK/ Kir3 subfamily assemble as heterotetramers to form cardiac I KACh channels (22).…”
Section: Significancementioning
confidence: 99%
“…Two subunits of the G-protein activated inwardly rectifying K + channels (GIRK1 and GIRK4) of the GIRK/ Kir3 subfamily assemble as heterotetramers to form cardiac I KACh channels (22). Indeed, both Girk1 −/− and Girk4 −/− mice lack cardiac I KACh (20,21,23). We recently showed that silencing of the hyperpolarization-activated current "funny" (I f ) channel in mice induces a complex arrhythmic profile that can be rescued by concurrent genetic ablation of Girk4 (24).…”
Section: Significancementioning
confidence: 99%
“…73 In the SA node, I KACh is responsible for vagal control of heart rate. 74 In atrial myocytes, I KACh contributes to repolarization and channel activation decreases action potential duration. I KACh inhibition prolongs the atrial refractory period without affecting the ventricles, making it an attractive target for drugs designed to treat AF.…”
Section: Kir21mentioning
confidence: 99%
“…Mice with genetic ablation of Kir3.1 or Kir3.4 are viable and lack any I KACh current. 78,74 Mice from both strains have normal resting heart rates, but significantly diminished vagal control of heart rate. Mice deficient in Kir3.4 were shown to be resistant to experimentally-induced AF.…”
Section: Kir21mentioning
confidence: 99%
“…GIRK channels are also important in the recovery of heart rate: GIRK4 knockout mice when exercised show a delay in the time taken to return to the resting heart rate [54]. This is intriguing as a delayed recovery of heart rate with exercise is associated with poor outcomes [55].…”
Section: G-protein Gated Inwardly Rectifying Potassium (Girk) Currentmentioning
confidence: 99%